Visualisasi Pengumuman dan SOP Fakultas Ilmu Komputer Universitas Katolik Santo Thomas Medan berbasis Multimedia - Laoly, Oktariani; Limbong, Tonni (LPPM UNIKA Santo Thomas Medan, 2018)
Standard Operational Procedure (SOP) is a collection of instructions that function as a guide in the process of administering government, especially the Faculty section that is in a university. Through the Standard Operational Procedure (SOP) to achieve its vision and mission. Students and Lecturers in the daily activities of the Faculty of Computer Science have functions and duties, rights and obligations that must be adhered to so that the process of academic activity in the lecture runs smoothly. Students in the Faculty of Computer Science are relatively old in understanding each line of each procedure in the announcement, so that the announcements from the Faculty often do not go as expected. What is not understood is not language but the flow of the activity procedure. To understand something better, it is necessary to provide an overview of multimedia-based visualization that describes the process part in conveying information or SOP announcements so that readers of the announcement can more easily digest the announcements submitted.